Experimental analysis of aluminium matrix composite material for braking application. (2021) - Nandhakumar, S.; Edwin Santhkumar, W.; Shunmughanaathan, V.K.
Abstract: Composite materials have become a popular material substitution for automotive, sports, medical, aerospace and other engineering fields due to their light-weight, high strength and/or stiffness of fibers. In this paper, a thermal analysis has been done to calculate the heat penetration time to analyze the brake fading condition. The purpose of the brakes is to retard or stop the vehicle in motion by converting the kinetic energy of the moving vehicle into rotational frictional torque at the brake shoes or brake pads. This energy will then change in to heat, the magnitude of the resulting temperature rise depends upon the braking application. The brakes should be able to dissipate large quantities of heat without undue temperature rise and should be rigid enough to absorb the large braking torques encountered. The feasibility of squeeze cast aluminium metal matrix composite for braking application has been studied using theoretical analysis. From the thermal analysis of MMC brake drum the temperature distribution is found to be lower as compared to the cast iron material. Theoretical results also show a very less heat penetration time for MMC brake drum as compared to cast iron brake drum. Because of less heat penetration time for MMC material from the analysis, it is found that in case of continuous braking the heat generated in the brake drum will be dissipated quickly and it will get cooled easily. Hence it is concluded that the problem of brake fading will not happen with in short period in MMC brake drum.